2022
DOI: 10.1039/d2ra03098e
|View full text |Cite
|
Sign up to set email alerts
|

Conversion of coal into N-doped porous carbon for high-performance SO2 adsorption

Abstract: The abundant pores of NCPCs provides adsorption sites for SO2. Nitrogen doping enhances the affinity energy of carbon to SO2 but reduces the amount of pores. A moderate N-doped coal-based porous carbon achieves SO2 capacity as high as 115 mg g−1.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 48 publications
0
2
0
Order By: Relevance
“…In another study, nitrogen-doped porous carbon was prepared by mixing a nitrogen source, specifically carbamide, with anthracite coal particles, along with the activating agent KOH. This mixture was then heated to carbonization temperatures ranging around 800 • C for 4 h. After carbonization, the chips were carefully washed, dried overnight, and subsequently utilized for the adsorption of sulphur dioxide (SO 2 ) [80].…”
Section: Synthesis Of Nitrogen-doped Adsorbentmentioning
confidence: 99%
“…In another study, nitrogen-doped porous carbon was prepared by mixing a nitrogen source, specifically carbamide, with anthracite coal particles, along with the activating agent KOH. This mixture was then heated to carbonization temperatures ranging around 800 • C for 4 h. After carbonization, the chips were carefully washed, dried overnight, and subsequently utilized for the adsorption of sulphur dioxide (SO 2 ) [80].…”
Section: Synthesis Of Nitrogen-doped Adsorbentmentioning
confidence: 99%
“…Dong et al 101 introduced N to modify CAC prepared by KOH activation of lignite and found that N doping can lead to rearrangement of the carbon skeleton structure, effectively improving the specific surface area and forming various N-containing functional groups on the surface of CAC. Wang et al 102 found that introducing N into CAC can effectively increase the specific surface area of CAC, thereby enhancing its SO 2 adsorption capacity. Chen et al 103 used KOH to activate coal liquefaction residue to prepare S-rich CAC.…”
Section: Modification Of Cacmentioning
confidence: 99%
“…13 Wang et al, developed a series of N-doped coal-based porous carbons (NCPCs) by calcining a mixture of anthracite, MgO, KOH and carbamide at 1073 K; their results showed that the balance between nitrogen doping content and specific surface area (microporosity) improved the number of active adsorption sites of SO 2 . 14 In this context, the carbon microfibers (CMFs) obtained by calcination of polyacrylonitrile microfibers (PANMFs) 15 present an opportunity for SO 2 detection due to the following aspects: (i) chemical composition based on nitrogen and oxygen functional groups resulting from the polymer precursor (PAN), (ii) high microporosity controllable depending on calcination temperature, (iii) good thermal stability, and (iv) reversible gas adsorption (e.g., CO 2 or CH 4 ). Concerning nitrogen functional groups, there have been identified four groups in the CMFs: N-6 (pyridine-N), N-5 (pyrrolic-N), N-X (pyridine-N-oxide) and N-Q (quaternary-N or graphitic-N).…”
mentioning
confidence: 99%